2013 IEEE Integrated STEM Education Conference (ISEC) 2013
DOI: 10.1109/isecon.2013.6525226
|View full text |Cite
|
Sign up to set email alerts
|

Conducting robots — Bridging the gap between science, technology and the arts in the undergraduate curriculum

Abstract: While many have explored multidisciplinary approaches to course content delivery in computer science and engineering, very few have combined engineering with fundamentally different disciplines such as the arts, humanities, or social science. This paper presents a multidisciplinary undergraduate seminar entitled "Conducting Robots" that brings together majors from four disparate disciplines: computer science, mechanical engineering, music, and interactive multimedia. The goal of the course is to teach and supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Other examples of combining arts and computing include Kim et al [7] where the authors describe the development of the Artbotics curriculum, and Brunvand and Stout [3] that describe a cross-disciplinary course for art and computer science and engineering students. However, as Salgian et al [10] conclude, there are few reported efforts on combining engineering with fundamentally different disciplines such as humanities or social sciences.…”
Section: Introductionmentioning
confidence: 99%
“…Other examples of combining arts and computing include Kim et al [7] where the authors describe the development of the Artbotics curriculum, and Brunvand and Stout [3] that describe a cross-disciplinary course for art and computer science and engineering students. However, as Salgian et al [10] conclude, there are few reported efforts on combining engineering with fundamentally different disciplines such as humanities or social sciences.…”
Section: Introductionmentioning
confidence: 99%